Germany : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The German economy has been experiencing as many setbacks as achievements. Continued wage moderation will be essential to aid recovery. Macroeconomic policies are limited by euro area constraints and the sizable public debt burden. Expenditure restraint is the cornerstone of the fiscal adjustment strategy. Labor market rigidities have proved the most intractable structural problem. Germany's record on product market liberalization is favorable and the reform momentum should be kept up. The quality of Germany's statistics is more than adequate for the purpose of effective surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet